Análise de expressão e splicing alternativo do gene Mdh-1 de Apis mellifera L. (Hymenoptera: Apidae) - Nagamati Junior, Keize (Universidade Federal de São Carlos, 2010)
Mdh-1 enzyme locus coding for cytoplasmic malate dehydrogenase has three common alleles Mdh-1100 (F), Mdh-180 (M) e Mdh-165 (S) and it has been extensively used as racial marker in populational studies of Apis mellifera. Additional isoforms are detected by electrophoretic analysis during ontogenetic development of A. mellifera, indicating differential expression of this locus, and a large set of evidences suggests that Mdh-1 alleles are under temperature-mediated selection. In this work, we proposed to study molecular aspects of this locus aiming to understand the nature of observed polymorphism and possible mechanisms leading to the formation of additional isoforms. Our results suggest Mdh-1100 as the ancestral allele that gave origin to alleles Mdh-180 and Mdh-165, and electrophoretic mobility differences of allelic products may be attributed to the substitution of a single aminoacid in each variant. Regarding genic expression during development, we re able to determine that both loci Mdh-1 and Mdh-2, coding for mitochondrial malate dehydrogenase, have high expression in larval and late pupal stages, and present a significant decrease in expression during transitional stages between larva and pupa. We also determined that additional isoforms are characteristic of pupae fat body and hemolymph, not being detected in other tissues, appearing at late larval stage and starting to disappear with beginning of pupal pigmentation. We were not able to identify the causes promoting the formation of the new isoforms, but our results suggest that this phenomenon is not due to alternative splicing or expression of a stage- and tissue-specific gene.
Keywords: Genética molecular; Expressão gênica; Fenotipagem; Malato desidrogenase; CIENCIAS BIOLOGICAS::GENETICA